Hubungan Anemia dan KEK dengan Kejadian BBLR - Mulianisaa, Rakhma; Tunggal, Tri; Suhrawardi, Suhrawardi (Midwifery Departement Poltekkes Kemenkes Banjarmasin, 2021)
Low Birth Weight (LBW) will become a global public health problem both in the short and long term. Based on data from the South Borneo Provincial Health Office. This study aims to determine the relationship between anemia and Chronic Energy Deficiency (CED) in pregnant women with LBW incident. Based on data from the Provincial Mortality Rate in South Borneo (2019) the highest cause was LBW with 226 cases with the highest overall in Hulu Sungai Selatan with 41 cases and Hulu Sungai Utara with 30 cases in pregnant women with LBW incident. Low birth weight can also be caused by factors of anemia and CED. This study aims to determine the relationship between anemia and Chronic Energy Deficiency (CED) in pregnant women with the incidence of Low Birth Weight (LBW)Methods: This research method uses the literature study method. The analysis uses descriptive . Analysis by taking 7 journals, namely 5 Nationals journals and 2 Internasional journals. The results of the research in 7 journals found LBW as much as (53% - 81,3%), CED as much as (16,7% - 96,8%), The results of statistical tests showed that there was a relationship between Anemia in pregnant women with LBW (p = 0,001; 0,000; 0,012; 0,000), a relationship between CED in pregnant women with LBW (p = 0,000; 0,023; 0,001; 0,001; 0,001). The conclusion of research from 7 journals is that there is a relationship between Anemia and Chronic Energy Deficiency (CED) in pregnant women with LBW incident it’s advisable to improve health service specifically at KIA, so that more information is provided about LBW during pregnancy checks so that pregnant women can take early prevention.Keywords: Incidence of Low Birth Weight, Anemia and Chronic Energy Deficiency in Pregnant Women